Upper West Side Catholics : Liberal Catholicism in a Conservative Archdiocese - Shelley, Thomas J. (Book collections on Project MUSE., 2020)
The history of Ascension parish is a microcosm of the history of the Catholic Church in New York City because it has been characterized by the two most powerful dynamics that have shaped the nature of New York Catholicism: immigration and neighborhood change.